2023
DOI: 10.1161/circresaha.122.321768
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessel Organoids for Development and Disease

Abstract: Despite enormous advances, cardiovascular disorders are still a major threat to global health and are responsible for one-third of deaths worldwide. Research for new therapeutics and the investigation of their effects on vascular parameters is often limited by species-specific pathways and a lack of high-throughput methods. The complex 3-dimensional environment of blood vessels, intricate cellular crosstalks, and organ-specific architectures further complicate the quest for a faithful human in vitro model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 122 publications
0
19
0
Order By: Relevance
“…To date, blood vessel organoids have been widely used in disease modeling (e.g., diabetic vasculopathy, COVID-19) [ 111 , 160 , 163 , 164 ]. Moreover, the multicellular feature of vessel organoids makes them a valuable tool for investigating the mechanisms of diseases [ 165 ]. For instance, one study demonstrated that SARS-CoV-2 can directly infect kidney and blood vessel organoids and the infection can be prevented by soluble recombinant human ACE2 (hrsACE2) antibodies, although which specific cell types are susceptible to SARS-CoV-2 infection remains unclear [ 163 ].…”
Section: Applications Of 3d Models In Cardiovascular Researchmentioning
confidence: 99%
“…To date, blood vessel organoids have been widely used in disease modeling (e.g., diabetic vasculopathy, COVID-19) [ 111 , 160 , 163 , 164 ]. Moreover, the multicellular feature of vessel organoids makes them a valuable tool for investigating the mechanisms of diseases [ 165 ]. For instance, one study demonstrated that SARS-CoV-2 can directly infect kidney and blood vessel organoids and the infection can be prevented by soluble recombinant human ACE2 (hrsACE2) antibodies, although which specific cell types are susceptible to SARS-CoV-2 infection remains unclear [ 163 ].…”
Section: Applications Of 3d Models In Cardiovascular Researchmentioning
confidence: 99%
“…Organoid technology has become increasingly important, especially for secondary prevention of T2DM [ 216 ]. Recent advances include human capillary vascular organoids, human islet-like organoids and engineered islets from stem cells, which offer promising avenues for diabetes research [ 217 219 ]. As research advances, we expect the creation of in vitro systems capable of simulating specific organ ECs.…”
Section: Experimental Models For Studying Macrovascular Complications...mentioning
confidence: 99%
“…63,69,70 Blood vessel organoids that can self-organize and reproduce angiogenesis have also been used as a model for disease processes in specific organs. 71 OOCs were also used to demonstrate the impact of interstitial flow on vasculogenesis and pathological angiogenesis. 63 In the design, ECs and stromal fibroblasts were cocultured to form a microvascular network with neovessel sprouting and angiogenic remodeling in response to interstitial flow (Figure 2C).…”
Section: Ooc Technology For Vascular Disease Modelingmentioning
confidence: 99%
“…Due to space limitations, we only mention a few representative examples here and invite readers to consult recent reviews on the topic. 7,11,71,113,114 Vascularized tumors on chip, particularly, have recently gained much attention, demonstrating the efficacy of OOCs for such complex interactions. 69,104,115 For instance, Heinrich et al 41 utilized a multilayered vascularized OOC model of pancreatic cancer to investigate fibrosis-induced compression of vasculature.…”
Section: Examples Of Vascular Disease Modeling-on-a-chipmentioning
confidence: 99%